2012
DOI: 10.5005/jp-journals-10031-1002
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries Prevalence among 3- to 14-Year-Old School Children, Uran, Raigad District, Maharashtra

Abstract: Schools remain an important setting offering an efficient and effective way to reach over 1 billion children worldwide and, through them, families and community members. This study is planned to assess the prevalence of dental caries in primary and secondary school students in rural area of Uran, so as to provide baseline data for planning intervention programs that will assist in reducing the prevalence of dental diseases. The study is designed to include 472 school children, which will be examined by basic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 8 publications
6
11
2
1
Order By: Relevance
“…This result is incompatible with Shingare et al that stated in mixed dentition period, DMFT caries experience was higher because of the anatomy of the tooth that had not been fully calcified and therefore more susceptible to caries [4].…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…This result is incompatible with Shingare et al that stated in mixed dentition period, DMFT caries experience was higher because of the anatomy of the tooth that had not been fully calcified and therefore more susceptible to caries [4].…”
Section: Resultscontrasting
confidence: 65%
“…An epidemiological survey of 472 normal children aged 7-14 years in India showed a fairly high caries prevalence, which was 80.92%. Results obtained showed that the mean DMFT scores at aged 7-10 and 11-14 years were 4.47 and 2.66 [4]. Several research also showed a high prevalence of caries in children with Down syndrome.…”
Section: Introductionmentioning
confidence: 88%
“…Similar study conducted by Poonam Shingare among 3 to 14 year old School Children in Uran Raigad District Maharashtra, showed the dental caries prevalence to be 80.92% with the mean DMFT/dmft to be 3.65. 11 Ramachandran karunakaran et al conducted a similar study in 460 male school going children of Namakkal district of Tamilnadu and found the prevalence of dental caries to be 69.57% with the mean dmft score of 2.89. 12 Datta P conducted similar study in school children of Sunderban district and found 68.8% male children of 13 & 14 years affected with dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] The prevalence and incidence of dental caries in a population is influenced by number of risk factors such as age, sex, ethnic group, dietary patterns and oral hygiene. 9 Dental caries is a disease with both high prevalence and severity in adult worldwide populations. 10 It affects over half of the population in industrialized countries and since it is a cumulative process, the number of affected individual's increases with ageing.…”
Section: Introductionmentioning
confidence: 99%